A lab-scale rotary kiln for thermal treatment of particulate materials under high concentrated solar radiation: Experimental assessment and transient numerical modeling. (August 2019) - Gallo, Alessandro; Alonso, Elisa; Pérez-Rábago, Carlos; Fuentealba, Edward; Roldán, María Isabel
Highlights: A solar rotary receiver was tested for particle heating to more than 800 °C. Applications are treatment of materials, industrial process heat or thermal storage. A fast transient numerical model was developed to quantify thermal losses and performances. Batch mode operation is demonstrated. Abstract: Rotary kilns are worldwide used for industrial processes that involve thermal treatments of particulate materials. However, a great amount of fossil fuels is employed in such processes. As alternative, solar rotary kilns are considered for this application due to their versatility and potential to substitute traditional fossil-fuel driven devices. In order to boost the development of this technology, efforts have to be focused on the control of the particle temperature during the treatment. In this context, a lab-scale rotary kiln was built and tested using a 7-kWe high-flux solar simulator at University of Antofagasta. It was conceived to treat particulate materials of different nature and it is able to reach temperatures higher than 800 °C under different operation strategies. Silicon carbide was selected for initial tests because it is inert, endures high temperatures (up to 1600 °C) and it has been proposed as thermal storage vector in several researches on concentrated solar power. In a first stage, the empty kiln was preheated up to about 800 °C, reaching a steady state in less than three hours and with a power of approximately 370 W entering the kiln cavity. Afterwards, 43 g of silicon carbide were introduced in the furnace and the system was heated again up to a second steady state above 800 °C. In this stage, particles showed a fast increment of their temperature and exceeded 700 °C in less than three minutes after loading. A one-dimensional transient numerical model was also developed to perform the thermal analysis of the kiln and the estimation of both the particle temperature and the system efficiency. Numerical results showed good agreement with experimental data and thermal losses could be quantified in detail. Therefore, the model was also used to predict the thermal behavior of a solar rotary kiln working in batch mode.